THE GENERALIZED ENTROPIC PROPERTY FOR THE MONO-n-ARY ALGEBRA - Ehsani, Amir (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
In this paper we show by using the laws of pseudo-distributivity that every idempotent and commutative algebra with one n-ary operation satisfying the generalized entropic property is entropic.